2014
DOI: 10.1007/s12640-014-9503-y
|View full text |Cite
|
Sign up to set email alerts
|

d-Methionine Protects Against Cisplatin-Induced Neurotoxicity in the Hippocampus of the Adult Rat

Abstract: The hippocampus plays an important role in memory, mood and spatial navigation. In the dentate gyrus of the adult hippocampus, in the subgranular zone (SGZ), new cells are generated that differentiate and mature into new neurons. Cisplatin, a highly effective antineoplastic drug with nephrotoxic and ototoxic side effects, induces apoptosis and suppresses neurogenesis in the hippocampus leading to memory impairment. Previous studies have shown that the antioxidant D-methionine protects against cisplatin-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…A typical loading dose of 100 mg/kg/day methionine was suggested to be tested in humans without any association with serious complications (39). The highest methionine dose of 800 mg/kg/day in mice in the current study was based on animal scaling (in which the 800-mg/kg/day dose in mice is ϳ12 times higher than the equivalent mg/kg dose in humans) (40) and information in the literature, where a comparable animal-scaled dose showed significant protective effects against oxidative stress-mediated toxicities in rats or guinea pigs following coadministration with other drugs, such as gentamicin and cisplatin (33,41,42). In considering the relative magnitude of the doses used, it is also important to recognize that the respective bioavailability following oral administration in humans and parenteral administration in the present and earlier animal studies is not known.…”
Section: Discussionmentioning
confidence: 99%
“…A typical loading dose of 100 mg/kg/day methionine was suggested to be tested in humans without any association with serious complications (39). The highest methionine dose of 800 mg/kg/day in mice in the current study was based on animal scaling (in which the 800-mg/kg/day dose in mice is ϳ12 times higher than the equivalent mg/kg dose in humans) (40) and information in the literature, where a comparable animal-scaled dose showed significant protective effects against oxidative stress-mediated toxicities in rats or guinea pigs following coadministration with other drugs, such as gentamicin and cisplatin (33,41,42). In considering the relative magnitude of the doses used, it is also important to recognize that the respective bioavailability following oral administration in humans and parenteral administration in the present and earlier animal studies is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The first researches on D-met properties focused on its efficacy in preventing cisplatin-induced ototoxicity in rat by its specific ability to counteract oxidative stress, without affecting the tumor response to an antineoplastic agent [112][113][114][115][116]. The D-met antioxidant activity is displayed also in other areas of the body: (i) in the liver, preventing the decrease of mitochondrial glutathione levels [117]; (ii) in the CNS, improving neurogenesis of hippocampal neurons [118]; (iii) in the kidney, through elevation of antioxidative activities [119]; and (iv) in the gastrointestinal system, protecting the mucosa and the gut microbiome from cisplatin-induced imbalance [120]. Recently, some evidences in the rat showed that D-met could alleviate skeletal muscle wasting caused by cisplatin, opening new perspectives in taking care of common and heavy side effects associated with anticancer platinum-based chemotherapy [121].…”
Section: D-methioninementioning
confidence: 99%
“…D-Methionine is also one of the effective antioxidant supplements against cisplatin-induced neurotoxicity in experimental animals. It showed a positive influence on the cortical neurons damage in an in vitro model of cortical networks [ 72 ], prevented the decreased neurogenesis in the hippocampus of the adult rats [ 73 ], regulated electrophysiological recordings, and increased hippocampal neurogenesis in rodents after cisplatin application [ 74 ]. According to Gopal et al [ 72 ], the optical isomer L-methionine was less protective on cisplatin-induced damage in cortical networks from mouse embryos compared to D-methionine.…”
Section: Antioxidants In the Treatment Of Platinum-based Chemothermentioning
confidence: 99%